Autophagic Turnover of Chloroplasts: Its Roles and Regulatory Mechanisms in Response to Sugar Starvation - Izumi, Masanori; Nakamura, Sakuya; Li, Nan (Frontiers in Plant Science, 2019)
Photosynthetic reactions in chloroplasts convert atmospheric carbon dioxide into starch and soluble sugars during the day. Starch, a transient storage form of sugar, is broken down into sugars as a source for respiratory energy production at night. Chloroplasts thus serve as the main sites of sugar production for photoautotrophic plant growth. Autophagy is an evolutionarily conserved intracellular process in eukaryotes that degrades organelles and proteins. Numerous studies have shown that autophagy is actively induced in sugar-starved plants. When photosynthetic sugar production is inhibited by environmental cues, chloroplasts themselves may become an attractive alternative energy source to sugars via their degradation. Here, we summarize the process of autophagic turnover of chloroplasts and its roles in plants in response to sugar starvation. We hypothesize that piecemeal-type chloroplast autophagy is specifically activated in plants in response to sugar starvation.